Flexible beam delivery of ultrafast laser through vacuum-pumped anti-resonant hollow-core fiber - Cai, Yiming; Mai, Yifan; Xiang, Shen; Shi, Jianhong; Zhu, Qixin; Li, Rong; Li, Jinyan; Li, Cheng; Yan, Dapeng; Xing, Yingbin (Frontiers in Physics, 2023)
We demonstrate a peak power of 100 MW ultrafast laser propagating through a 5-m anti-resonant hollow-core fiber (AR-HCF). The AR-HCF consists of a 45-μm-hollow-core and seven untouched capillaries. The attenuation of 0.11 dB/m is measured at a wavelength of 1030 nm. A pumpable armored tube is designed for air exhaust to suppress self-phase modulation (SPM) and enable ultrafast laser flexible beam delivery while maintaining its input parameters. The transmission beam modes and the comparison between the laser beam characteristics after transmission under air-filling and vacuum pumping HCF are discussed. With the suppression of air concentration, the transmission efficiency increases from 61% to 72% and pulse distortion is effectively controlled.